2019
DOI: 10.51985/jbumdc2018106
|View full text |Cite
|
Sign up to set email alerts
|

Estimation Of Salivary Superoxide Dismutase Level In Oral Submucous Fibrosis: A Clinical And Biochemical Study

Abstract: Objective: The objective of the study was to compare the salivary Superoxide dismutase (mU/L) level among stage one patients of Oral sub mucous fibrosis and healthy controls. Study Design and Setting: It was a comparative cross sectional study design conducted at Outpatient clinic of Dental Department at Ziauddin University Hospital from January 2012 till December 2013. Methodology: Eighty histo-pathologically confirmed patients of clinical stage one Oral Sub mucosal fibrosis (OSMF) and eighty healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Another study showed that saliva SOD levels in patients with OSMF decreased significantly, which to some extent reflected the decline of antioxidant capacity in patients with OSMF. Researchers found that mouth opening in OSMF patients decreased with the decrease of SOD levels [31] .…”
Section: Oral Submucosal Fibrosis and Oxidative Stressmentioning
confidence: 99%
“…Another study showed that saliva SOD levels in patients with OSMF decreased significantly, which to some extent reflected the decline of antioxidant capacity in patients with OSMF. Researchers found that mouth opening in OSMF patients decreased with the decrease of SOD levels [31] .…”
Section: Oral Submucosal Fibrosis and Oxidative Stressmentioning
confidence: 99%